Mind the gap! Differences between parents’ childhood games and their children’s game preferences - Balci, Sibel; Ahi, Berat (SAGE Publications, 2017)
This study discusses the differences between parents’ childhood games and their children’s game preferences. Four hundred and nineteen parents were surveyed to determine their play experiences as children as well as their children’s play experiences today. The results of the study indicate that there is a gap between the time spent outdoors by parents in their childhood and their children. Today, most children spend time indoors, usually playing computer games. The activities and games preferred by the children differed from those of their parents. Although the parents preferred mostly group games requiring group cooperation, competition between groups and physical activity, the children preferred more individualized activities such as cycling and playing in the park. The factors hindering children from playing outside are considered. Although most parents indicated that playing outside is beneficial for their children, they prevented their children from playing outside for reasons such as the dangers of being hit by a car or abduction.
Keywords: Education & Educational Research; 4. Education